INVESTIGATING PRESERVICE SECONDARY MATHEMATICS TEACHERSâ PEDAGOGICAL CONTENT KNOWLEDGE: A CASE STUDY IN MICROTEACHING COURSE - Rianasari, Veronika Fitri (AdMathEdu : Mathematics Education, Mathematics, and Applied Mathematics Journal, 2017)
Effective teachers have a deep knowledge about the content of the subject matter they teach. As well as a deep knowledge of the material being taught, teachers must also have a deep knowledge about the processes and practices of teaching and learning. Pedagogical content knowledge is the intersection of discipline specific subject content knowledge and pedagogical knowledge. The purpose of this study is to examine Pedagogical Content Knowledge (PCK) of 30 preservice secondary mathematics teachers in microteaching course. The participants of this research are third-year preservice secondary mathematics teachers at Sanata Dharma University undertaking microteaching course. The data were collected in the form of observation, quesstionare, and written document. During the microteaching course, researcher observed preservice teachersâ comprehension of PCK components. The observation sheet is designed based on the conceptual framework for analysing PCK developed by Chick, Baker, Pham, and Cheng (2006). The findings revealed that many students have developed their PCK. However there were also some skills and knowledge that should be improved.Â Keywords: preservice secondary mathematics teachers, PCK, microteaching